Contractile Behavior of Mouse Aorta Depends on SERCA2 Isoform Distribution: Effects of Replacing SERCA2a by SERCA2b - Fransen, Paul; Chen, Jialin; Vangheluwe, Peter; Guns, Pieter-Jan (Frontiers in Physiology, 2020)
The Sarco(endo)plasmic reticulum Ca2+ ATPase (SERCA) actively pumps Ca2+ into the sarco/endoplasmic reticulum, thereby regulating intracellular Ca2+ concentrations and associated physiological processes. Different SERCA isoforms have been described (SERCA1, 2 and 3) with SERCA2 playing a pivotal role in Ca2+ homeostasis in cardiovascular tissues. In the heart, SERCA2a is the dominant isoform and has been proposed as therapeutic target in patients with heart failure. In the vasculature, both SERCA2a and SERCA2b are expressed with SERCA2b being the predominant isoform. The physiological role of SERCA2a in the vasculature, however, remains incompletely understood. In the present study, we used gene-modified mice in which the alternative splicing of the SERCA2-encoding gene (Atp2a2), underlying the expression of SERCA2a, is prevented and SERCA2a is replaced by SERCA2b. The resulting SERCA2b/b mice provide a unique opportunity to investigate the specific contribution of SERCA2a versus SERCA2b to vascular physiology. Aortic segments of SERCA2b/b (SERCA2a-deficient) and SERCA2a/b (control) mice were mounted in organ baths to evaluate vascular reactivity. SERCA2b/b aortic rings displayed higher contractions induced by phenylephrine (1 µM). Surprisingly, the initial inositol-3-phosphate mediated phasic contraction showed a faster decay of force in SERCA2b/b mice, while the subsequent tonic contraction was larger in SERCA2b/b segments. Moreover, in the presence of the calcium channel blocker diltiazem (35 µM) SERCA2b/b aortic rings showed higher contractions compared to SERCA2a/b, suggesting that SERCA2a (deficiency) modulates the activity of non-selective cation channels. Additionally, in endothelial cell (EC)-denuded aortic segments, the SERCA-inhibitor cyclopiazonic acid (CPA) caused markedly larger contractions in SERCA2b/b mice, while the increases of cytosolic Ca2+ were similar in both strains. Hence, aortas of SERCA2b/b mice appear to have a stronger coupling of intracellular Ca2+ to contraction, which may be in agreement with the reported difference in intracellular localization of SERCA2a versus SERCA2b. Finally, EC-mediated relaxation by acetylcholine and ATP was assessed. Concentration-response-curves for ATP showed a higher sensitivity of aortic segments of SERCA2b/b mice, while no difference in potency between strains were observed for acetylcholine. In summary, despite the relative low expression of SERCA2a in the murine aorta, our results point towards a distinct role in vascular physiology.